(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Akintunde AO, Ndubuisi-Ogbonna LC, Oyekale OO, Shobo BA, Animashaun RO, Adewumi AG. 2024. Nutritional evaluation of aqueous extracts of Parquetina nigrescens leaves for physiological manipulations of livestock feed. Asian J Agric 8: 95-103. Plant extracts increase good bacteria’s growth while reducing harmful bacteria’s activity in the gastrointestinal tract. The Aqueous Extract of Parquetina nigrescens (Wennberg) Bullock Leaves (AEPNL) was evaluated for nutritional and phytochemical compositions. Therefore, 50 g of the leaves was blended with 1,000 mL of water and filtered. The filtrate was then analyzed for its nutritional contents. The results revealed that AEPNL contained crude protein (24.60%), crude fiber (5.60%), crude ash (3.60%), carbohydrate (62.30%), and crude fat (2.60%). AEPNL contained appreciable amounts of essential and non-essential amino acids. AEPNL contained minerals: Calcium (23.90 mg/100g), iron (3.60 mg/100g), magnesium (4.05 mg/100g), phosphorus (6.88 mg/100g), potassium (23.21 mg/100g), chlorine (0.33 mg/100g), manganese (1.46 mg/100g), sodium (0.36 mg/100g), aluminum (4.34 mg/100g), silicon (29.70 mg/100g) and titanium (2.17 mg/100g) and vitamins: A (2.30 mg/100/g) B1 (275.20 mg/100g), B2 (855.30 mg/100g), B3 (328.20 mg/100g), C (16.20 mg/100g) and E (0.012 mg/100g). Phytochemical evaluation showed high amounts of alkaloids (8.20 mg/100g), low amounts of flavonoids, glycosides, steroids, phenols, terpenoids and anthraquinones (2.20 mg/100g, 0.06 mg/100g, 0.20 mg/100g, 0.86 mg/100g, 0.52 mg/100g and 1.55 mg/100g respectively) and moderate amounts of saponin and tannin (5.20 mg/100g and 6.30 mg/100g respectively). It can be concluded that AEPNL is of high nutritional quality with the resultant phytochemicals that could serve as supplements with huge potential in the manipulations of physiological activities of poultry and livestock species.